KAU Mithra-Yard long bean variety promising for riverine alluvium of Central Travancore regions - Kuriokose, Jessy M.; Rakhi, R.; Jayakumar, G.; Indira, M.; Shajan, V. R.; Rini, C. R. (Journal of Tropical Agriculture, 2022)
Agricultural Research Station, Thiruvalla initiated an experiment during 2013 to evolve suitable yard long bean (YLB) variety for the riverine belts of Central Travancore region. Twelve accessions collected were continuously evaluated for their growth characters, yield traits and quality parameters. Among these, YLB 5 performed well in yield trials and farm trials. It recorded high green pod yield per hectare (20.72t/ha) with good shelf life and cooking quality. It has trailing growth habit with green stem and petiole. It also had attractive long light green pods having an average pod length of 78.60 cm. The accession was found to be promising and suitable for riverine alluvium of Upper Kuttanad region and therefore was released with the name ‘KAU Mithra’ by Kerala Agricultural University in 2018.